Age at menarche and body fat in adolescent girls - Aman Bhakti Pulungan; Resyana Putri Nugraheni; Najib Advani; Arwin AP Akib; Yoga Devaera; Hikari Ambara Sjakti; Attika Adrianti Andarie (Paediatrica Indonesiana, 2020)
Background Menarcheal age is important in adolescent girls due to its associations with health outcomes at adulthood. Modifiable factors that may influence menarcheal age include body fat mass and fat distribution. Objective: To investigate possible correlations between body fat mass and fat distribution with age at menarche in adolescent girls. Methods This study was a cross-sectional study on 32 girls aged 10-15 years in Central Jakarta, who experienced menarche within the time period of July to September 2019. Data on menarcheal age was collected by recall. Body fat mass and distribution were calculated using anthropometric measurements and bioelectrical impedance analyzer (BIA) results. Results The mean age of study subjects was 12.06 (SD 0.82) years and the mean age at menarche was 11.91 (SD 0.83) years. Correlation tests revealed a moderate negative correlation between body mass index-for-age and menarcheal age (r= -0.45; P=0.01) and weak negative correlation between waist-height ratio and menarcheal age (r= -0.37; P=0.03). Conclusion Menarcheal age is correlated with body mass index-for-age and waist-height ratio. However, no significant correlations between menarcheal age and body fat mass or distribution are found.